2021
DOI: 10.1016/j.lfs.2021.119437
|View full text |Cite
|
Sign up to set email alerts
|

Nanocurcumin improves Treg cell responses in patients with mild and severe SARS-CoV2

Abstract: In Coronavirus disease 2019 (COVID-19), a decreased number of regulatory T (Treg) cells and their mediated factors lead to a hyperinflammatory state due to overactivation of the inflammatory cells and factors during the infection. In the current study, we evaluated the Nanocurcumin effects on the Treg cell population and corresponding factors in mild and severe COVID-19 patients. To investigate the Nanocurcumin effects, 80 COVID-19 patients (40 at the severe stage and 40 at the mild stage) were selected and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 49 publications
(33 reference statements)
2
64
0
1
Order By: Relevance
“…Besides, golden spice turmeric ( Curcuma longa ), which is a classic ingredient of Asian food that has become popular in Western societies, due to its immunomodulatory, antioxidant and anticancer capacities, also seems to have anti-SARS-CoV-2 effects. This fact is not surprising, and it is mainly related to the presence of curcumin, as already described by several in vitro and clinical studies [ 98 , 99 , 100 ]. The administration of 140 mg of nano-curcumin showed having a modulating effect in COVID-19 patients ( Table 2 ) by suppressing the expression of genes involved in the pro-inflammatory cytokines IL-1 β and IL-6, IL-18, and TNF-α production [ 99 ].…”
Section: Uptake Of Phenolic Compounds In Dietary Supplements In Covid-19mentioning
confidence: 56%
See 1 more Smart Citation
“…Besides, golden spice turmeric ( Curcuma longa ), which is a classic ingredient of Asian food that has become popular in Western societies, due to its immunomodulatory, antioxidant and anticancer capacities, also seems to have anti-SARS-CoV-2 effects. This fact is not surprising, and it is mainly related to the presence of curcumin, as already described by several in vitro and clinical studies [ 98 , 99 , 100 ]. The administration of 140 mg of nano-curcumin showed having a modulating effect in COVID-19 patients ( Table 2 ) by suppressing the expression of genes involved in the pro-inflammatory cytokines IL-1 β and IL-6, IL-18, and TNF-α production [ 99 ].…”
Section: Uptake Of Phenolic Compounds In Dietary Supplements In Covid-19mentioning
confidence: 56%
“…Another study also observed that the percentage of deceased patients in the control group was lower (40%, 8 out of 20) compared to the group treated with nano-curcumin (20%, 4 out of 20). The treatment with nano-curcumin has also been shown to be capable of increasing the count of Treg cells, anti-inflammatory cytokines IL-10 and IL-35, and transforming growth factor (TGF)- β in bloodstream, as well as the expression of their related genes, being another evidence regarding the usefulness of this treatment in regulating the immune response and the severity of the disease [ 99 , 100 ].…”
Section: Uptake Of Phenolic Compounds In Dietary Supplements In Covid-19mentioning
confidence: 99%
“…Regulatory T cells possess an immunoregulatory role in SARS-CoV-2 infection due to the production of anti-inflammatory cytokines and contact-mediated cellular suppression. Levels of these T subset cells are also decreased in patients with both mild and severe forms of the infection [48,116,132]. An interesting observation was registered by Vick et al [133], who confirmed an increased frequency of Tregs expressing activation and suppression markers CTLA-4, ICOS, Ki67, HLA-DR/CD38, and PD-1 in patients with respiratory viruses compared to healthy donors.…”
Section: T Cell Responses-are Fewer Emphasized Subsets Of T Cells and T Exhaustion Crucial For The Course Of Covid-19 Infection?mentioning
confidence: 90%
“…136 Compared to the placebo group, curcumin could reduce the frequency of Th17 cells, Treg and their related inflammatory factors in both mild and severe COVID-19 patients. 137,138 In addition to antiinflammatory effect, curcumin can also play an antiviral role by inhibiting SARS-CoV-2 entry into cells and inhibiting viral proliferation. Curcumin has a variety of pharmacological effects and high safety, which makes it an adjunctive drug for the treatment of COVID- 19.…”
Section: Effect Of Curcumin On Covid-19mentioning
confidence: 99%